Learning to lead: Segmentation of attendees to a Christian leadership conference. Issue 1 (26th October 2016) - Tkaczynski, Aaron; Arli, Denni; Hussey, Ian
Abstract : Christian leadership conferences are religious events in which attendees can improve their leadership skills in their current or potential area of ministry. Despite considerable anecdotal evidence, there is limited empirical research that has determined why attendees are motivated to attend these events and if they can be differentiated based on their personal characteristics and year of event attendance. To address these research gaps, 335 questionnaires were collected at an Australian Christian leadership conference during the 2013 and 2014 events. To better equip me in my current leadership role and to feel encouraged to learn more about God were the two dominant motivations identified by respondents, regardless of the year of data collection. Motivational differences also existed based on respondents' personal characteristics. This study has provided theoretical and practical implications for religious nonprofit organizations relating to these issues and provides future research opportunities.